2022
DOI: 10.21037/qims-21-980
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of novel radiomics-based nomograms for the prediction of EGFR mutations and Ki-67 proliferation index in non-small cell lung cancer

Abstract: Background: We developed and validated novel radiomics-based nomograms to identify epidermal growth factor receptor (EGFR) mutations and the Ki-67 proliferation index of non-small cell lung cancer. Methods:We enrolled 132 patients with histologically verified non-small cell lung cancer from four hospital institutions who underwent computed tomography (CT) scans. EGFR mutations and the Ki-67 proliferation index were measured from tumor tissues. A total of 1,287 radiomic features were extracted, and a three-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Similar to previous findings, inverse variance and skewness were included among radiomics features in the EGFR prediction model, 25,36 and among clinical features, smoking history and sex were used in the EGFR mutation prediction model 32,37 . In the KRAS group, smoking history was excluded from the final model, which is inconsistent with some studies, 38,39 suggesting that smoking history may be an influencing factor when predicting KRAS mutation status in patients with NSCLC, but not in patients with EGFR − tumors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar to previous findings, inverse variance and skewness were included among radiomics features in the EGFR prediction model, 25,36 and among clinical features, smoking history and sex were used in the EGFR mutation prediction model 32,37 . In the KRAS group, smoking history was excluded from the final model, which is inconsistent with some studies, 38,39 suggesting that smoking history may be an influencing factor when predicting KRAS mutation status in patients with NSCLC, but not in patients with EGFR − tumors.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, three multicenter studies [30][31][32] predicted EGFR mutation status using radiomics based on CT images. The number of patients enrolled was 132, 194, and 636, and the AUCs of the validation set were 0.80, 0.77, and 0.803, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4). Dong et al (16) achieved the highest RQS of 19 (52.78%), while Gu et al (21) scored the lowest with 1 (2.78%). These results underscore the importance of rigorous and standardized reporting in radiomics studies.…”
Section: Resultsmentioning
confidence: 97%
“…Most studies in our review demonstrated a strong preference for logistic regression models in their radiomic analysis, with some incorporating additional methodologies for enhanced robustness and precision (1214, 1618, 20). In contrast, Zhu et al and Sun et al diversified their approach by integrating logistic regression with decision trees, support vector machines (SVM), and adaboost (15, 19).…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies were designed retrospectively, conducted in China, and used CT scans as the only imaging modality. Seven studies were conducted at single-center institutions (29, 30,[33][34][35][36]38), while three studies adopted a multicenter approach (31,32,37). Three studies used contrast-enhanced CT scans for their images (30,33,35).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%